Ethological characteristics of the primary depressive episode - Khomitskyi, M.; Makoid, V. (Journal of Education, Health and Sport, 2022)
Significant polymorphism of the clinical picture of depression and certain contradictions of scientific views on the nosological specificity of these conditions complicate the establishment of specific clinical and psychopathological signs of endogenous and psychogenic depression, their typology, dynamics, prognosis, which makes the study of nonverbal behavior relevant and promising task. The purpose of the study was to establish the psychopathological and clinical-ethological manifestations of the primary depressive episode and to conduct a comparative analysis of endogenous and psychogenic variants of the primary depressive episode. Contingents and methods. Based on the principles of bioethics, 96 patients (49 men and 47 women) with primary depressive episode – main group – who applied for outpatient psychiatric department of Zaporizhzhia regional psychiatry clinic in 2018-2021 were clinically examined. Diagnostic conclusions were made in accordance with the ICD-10 criteria. The control group consisted of 35 mentally healthy individuals, comparable in age and gender composition with the study group. Results. Patients with mild and moderate severity of the primary depressive episode are characterized by sad look, poses of reflection, submission, concentration in combination with facial expressions of suffering, guilt, helplessness, pensiveness, sideways, wrinkles on the forehead, stereotyped hand movements, head, head, reducing the synchronicity of gestural, facial and motor components of motility; avoidance of contacts and a sharp decrease in reactions to external influences. Severe manifestations of depression are characterized by sad and mournful facial expressions, lowered corners of the mouth, quiet voice, motor retardation, facial expressions of suffering, guilt and shame. Conclusion. The ethological component of the clinical-psychopathological method, based on the description of nonverbal behavior, can significantly improve the diagnostic capabilities of early detection of depressive episode, provides additional tools for typological differentiation and severity of patients with primary depressive episode.